NILAI KEARIFAN LOKAL DALAM TRADISI BEKARANG DI DESA JAMBI KECIL - Muntaha, Afif; Soedarto, Harry; Rustam, Rustam; Akhyaruddin, Akhyaruddin (Ensiklopedia of Journal, 2023)
Abstract: The purpose of this research is to describe the form of the "bekarang" tradition in Jambi Kecil Village, and to describe the local wisdom values contained in the "Bekarang" tradition in Jambi Kecil Village. This research is a qualitative research that aims to find out the form of the "Bekarang" tradition in Jambi Kecil Village and describes the values of local wisdom contained in the Bekarang tradition. Research data collection techniques, namely observation techniques, interview techniques and documentation techniques. Then the data obtained were analyzed using content analysis and tested through method triangulation. The results of this study are the "Bekarang" Tradition is a tradition of catching fish. The implementation of this activity includes several stages, namely notification to local residents, time planning, preparation and implementation. The most prominent characteristic in the implementation of this tradition is the attitude of togetherness between communities in the preparation for the implementation of this recent tradition. The "Bekarang" tradition also embodies the characteristics of gotong royong, that is, togetherness does work voluntarily and creates a sense of kinship and brotherhood among people. The values of local wisdom in the "Bekarang" tradition include values, among these values are religious values, mutual cooperation values, aesthetic values, and social values. Keywords: Bekarang Tradition, Local wisdom values, Jambi Kecil.